1997
DOI: 10.1093/sleep/20.7.523
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Characteristics and Principal Component Structure of the Hypnagogic EEG

Abstract: The purpose of the present study was to identify the dominant topographic components of electroencephalographs (EEG) and their behavior during the waking-sleeping transition period. Somnography of nocturnal sleep was recorded on 10 male subjects. Each recording, from "lights-off" to 5 minutes after the appearance of the first sleep spindle, was analyzed. The typical EEG patterns during hypnagogic period were classified into nine EEG stages. Topographic maps demonstrated that the dominant areas of alpha-band ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 14 publications
10
68
2
1
Order By: Relevance
“…For example, since the pioneering study of Dement and Kleitman (1957), it has been known that during the transition from alert wakefulness to sleep onset (i.e., the hypnagogic state), ␣ power decreases and and ␦ power increase. These findings have been replicated in a more recent study (Tanaka et al, 1997). In line with previous findings, Cajochen et al (in Klimesch, 1999) have shown that administration of melatonin, which regulates waking and sleeping and increases sleepiness, leads to an increase in the band and a decrease in the ␣ band.…”
supporting
confidence: 79%
“…For example, since the pioneering study of Dement and Kleitman (1957), it has been known that during the transition from alert wakefulness to sleep onset (i.e., the hypnagogic state), ␣ power decreases and and ␦ power increase. These findings have been replicated in a more recent study (Tanaka et al, 1997). In line with previous findings, Cajochen et al (in Klimesch, 1999) have shown that administration of melatonin, which regulates waking and sleeping and increases sleepiness, leads to an increase in the band and a decrease in the ␣ band.…”
supporting
confidence: 79%
“…VIGALL takes into account the vigilance stages as described by authors such as Bente [18], Roth [19] and Loomis et al [20] and more recently by others [21,22,23,24,25]. In short, vigilance stages range from stage 0 (corresponding to high alertness) to stages A1, A2 and A3 (corresponding to relaxed wakefulness) and further to stages B1 and B2/3 (corresponding to increasing drowsiness) and finally to stage C (sleep onset).…”
Section: Methodsmentioning
confidence: 99%
“…Many efforts have been directed toward differentiating stage 1 from wakefulness and stage 2 focused on the process of falling asleep, and although the precise moment of sleep onset is still a matter of debate, detailed studies have been carried out to determine the precise entrance into sleep considering behavioral, physiological and subjective changes (Ogilvie et al, 1991;Hasan and Broughton, 1994;Wright et al, 1995;Tanaka et al, 1997). In contrast, little is known about differences in EEG activity between stage 1 and REM sleep, except for a couple of studies focused on alpha activity only (Armitage, 1995;Cantero et al, 1999).…”
Section: Introductionmentioning
confidence: 99%